Perbandingan Metode Audio Dan Audio Visual Terhadap Pengetahuan Tentang Pemeriksaan Payudara Sendiri (SADARI) Pada Remaja Putri - Izza Swestivioka; Iroma Maulida; Nora Rahmanindar (SEAJOM: The Southeast Asia Journal of Midwifery, 2019)
Breast self-examination is a simple and good filtration technique for early detection of symptoms of breast disorders. Counseling is a necessary intervention to improve knowledge about SADARI. The purpose of this research is to know the influence of media types of communication with the knowledge in the young women in a high school in TEGAL. This was a Quasi Experimental Study. The population of this research is 60 young girls. The sampling method is taken randomly. Respondents were divided into two groups: the group of students who got information through audio visual media (video) and the group who got information through audio. Statistical analysys using T test. The results of this study showed that both types of extension methods affect the knowledge with Independent Sample T-Test obtained significance value 0.000 (P value < 0.05). The average knowledge in the group is 85.70 while the group that uses audio media has an average knowledge with a score of 73.83. This research demonstrates the implementation of awareness about Breast self examination on young girls can increase knowledge in about signs and symptoms of disorders in the breast.